An ensemble of daily simulated runoff data (1981–2099) under climate change conditions for 93 catchments in Switzerland (Hydro‐CH2018‐Runoff ensemble). (25th March 2021) - Muelchi, Regula; Rössler, Ole; Schwanbeck, Jan; Weingartner, Rolf; Martius, Olivia
Abstract: We present a new ensemble of daily runoff simulations for meso‐scale catchments in Switzerland for the period 1981–2099: The Hydro‐CH2018‐Runoff ensemble. The ensemble contains runoff simulations for 93 catchments in Switzerland covering a wide range of different catchment characteristics governed by pluvial, nival and glacial runoff regimes. The hydrological modelling system PREVAH was thoroughly calibrated and validated for each catchment. The simulations show satisfactory performance with a median Nash‐Sutcliffe efficiency of 0.82 in the calibration and validation period. The calibrated parameters were then used to simulate runoff under climate change for each of the 93 catchments. These simulations were driven by the high‐resolution new Swiss climate change scenarios (CH2018) consisting of 68 GCM‐RCM combinations covering 3 different emission scenarios: RCP2.6, RCP4.5 and RCP8.5. The simulations show good agreement between simulated and observed runoff regimes in the reference period. The Hydro‐CH2018‐Runoff ensemble is publicly available under http://doi.org/10.5281/zenodo.3937485 (Muelchi, R., Rössler, O., Schwanbeck, J., Weingartner, R., and Martius, O. (2020) Hydro‐CH2018‐Runoff ensemble (version v1). Zenodo) and can be used for further impact studies. Abstract : The Hydro‐CH2018‐Runoff data set are the official new hydrological climate change scenarios for Switzerland that will be the basis for subsequent impact studies. The data set contains daily runoff simulations (1981‐2099) for 93 catchments in Switzerland. A description of the data set along with the underlying methods is provided to ensure transparency for future reuse.